Investigating mosquito innate immune defence mechanism towards malaria vaccine development - Feisal Mohammed (International Journal of Insects, 2026)
Mosquito-borne diseases weigh heavily on public health across the globe. The mosquito’s innate immune system certainly decides whether malaria parasites survive inside the vector, and that sighted it as a logical place to discover new vaccine ideas. In this review, we examine how Anopheles mosquitoes defend themselves against Plasmodium parasites and how those defenses could be turned into tools for malaria control. We focus on three layers of immunity: antimicrobial peptides that attack invaders directly, reactive oxygen species that create a hostile oxidative environment, and physical barriers like the peritrophic matrix that block parasites in the midgut. We also consider antioxidant enzymes that mosquitoes use to manage their own oxidative stress during infection, because that balance influences parasite success. Beyond the midgut, mosquito salivary proteins are drawing attention as vaccine targets, though saliva-based approaches come with practical and immunological hurdles. A clearer picture of mosquito immune pathways, the genes that drive them, and the vector’s physiology could open faster routes to transmission-blocking vaccines.
Keywords: Innate immunity; Malaria Vaccine; Mosquito; Plasmodium; Vector Biology; parasite